Food lit a reader's guide to epicurean nonfiction - Stoeger, Melissa Brackney (Santa Barbara, California Libraries Unlimited, 2013)
"An essential tool for assisting leisure readers interested in topics surrounding food, this unique book contains annotations and read-alikes for hundreds of nonfiction titles about the joys of comestibles and cooking"-- Provided by publisher.
Food memoirs and autobiographies -- Food biographies -- Food travel -- Food adventure -- History of food -- Food science -- Investigative food writing -- Narrative cookbooks -- Food essays.
Keywords: Food -- Bibliography